If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(p + 5) = 0 Reorder the terms: 7(5 + p) = 0 (5 * 7 + p * 7) = 0 (35 + 7p) = 0 Solving 35 + 7p = 0 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-35' to each side of the equation. 35 + -35 + 7p = 0 + -35 Combine like terms: 35 + -35 = 0 0 + 7p = 0 + -35 7p = 0 + -35 Combine like terms: 0 + -35 = -35 7p = -35 Divide each side by '7'. p = -5 Simplifying p = -5
| (2*5)=180 | | X-2y=3x+4 | | 1.5x+19=2.27x+15 | | 34r+34=8(5r-1) | | 120=(n-2)180 | | x+111=79 | | -18=-9x | | 5+5=10+2 | | 1.5x+19=2.27+15 | | g-.75=-.6 | | 5(m)=67 | | 8m-5=-5-2m-m | | 3p-6=2q | | 50.45x+60=50.95 | | x^3+4x+80=0 | | -.07y-1.6=2.1y+1.2 | | 2x+3y=5x-2y+7 | | Kx(X-6)=2 | | .13x+X=20.34 | | 2.5r=120 | | 7.7a+11=72.6 | | 7+55x=33x+19 | | 5+5=2 | | (.2y)*y=.45 | | -8h+2h-10=-28 | | 3.5(-83x-3)=3.7(7x-30) | | 2x=3x-23 | | y=-16x^2+12x+0.2 | | x+29=51 | | y-5=-9(x-4) | | X^3y^2+3X^2y-28X=0 | | -0.72E-4= |